Life of Inland Waters An Elementary Text Book of Fresh-Water Biology For Students - Needham, James G. (Cornell University Press, 2019)
This work is a textbook of fresh-water life dealing with its forms, its conditions, its fitnesses, its associations, and its economic aspects. The ecologic side of fresh-water biology is emphasized. Due consideration is given to the educational, economic, sanitary, social, civic, and aesthetic aspects of the subject.Limnology in America today is in its infancy. The value of its past achievements is just beginning to be appreciated. The benefits to come from a more intensive study of water life arc just beginning to be disclosed. That there is a widespread interest is already manifest in the large number of biological stations at which limnological work is being done.We recommend this volume as a general introduction to all students and teachers of this subject.